POLA, PERILAKU DAN PRAKTEK KOMUNIKASI ISLAM PADA KELOMPOK TRADISIONAL DALAM MENGAKSES MEDIA ONLINE - Dian Marhaeni K; Urip Mulyadi (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2017)
This research focuses from the uniqueness and specificity of traditional group communication in accessing online media. By using qualitative descriptive analysis the researcher reveal the phenomenon of Islamic behavioral pattern, behavior and practice of communication in traditional group. Theoretical studies were conducted by exploring theories about communication patterns, communication behavior and Islamic communication practices from various sources. The research method is done by appointing informants according to the criteria and objectives of the research and selecting groups of informants by purposive and snowball system. Primary data experience the process of reduction and presentation of data with Miles and Huberman analysis to get good data quality. This study resulted in the conclusion that there are two-stage communication pattern for certain types of communication, the centralistic communication pattern and the wheel network. There is a strong client-client relationship in this group. The relationship affects content and communication behavior in online media. A future recommendation for subsequent research is to focus on the traditional group communication behavior in business nd sales transactions.